Measurement of Serum Osteopontin and Interleukin-17 in Asthmatic Children in Saudi Arabia - Alzahrani, Ali Khairallah; Mohammed, Nader Mohammed; Al-Swat, Humaid; Karam, Rehab Ahmed (Journal of Pediatric Biochemistry, 2015)
Cytokines play an important role in the pathophysiology of asthma by affecting airway remodeling and allergic reactions. We aimed to measure the serum concentrations of osteopontin (OPN) and interleukin (IL)-17 in a group of asthmatic and normal children to test the association of these two cytokines with the severity of asthma in Saudi children. Our study included 50 asthmatic and 50 normal children. Serum cytokines were measured by ELISA technique. Pulmonary function tests were performed in the asthmatic children. Serum levels of OPN and IL-17 were significantly increased in asthmatic children in comparison to control group. Also, the concentrations of OPN and IL-17 were significantly associated with asthma severity. There was a significant positive correlation between OPN and IL-17 levels. In conclusion, our study suggests that OPN and IL-17 may play a role in childhood asthma and are strongly related to the disease severity.
Keywords: interleukin-17; osteopontin; bronchial asthma